Enzymatic surface hydrolysis of poly(ethylene terephthalate) and bis(benzoyloxyethyl) terephthalate by lipase and cutinase in the presence of surface active molecules - Eberl, A. (2009)
A lipase from Thermomyces lanuginosus and cutinases from Thermobifida fusca and Fusarium solani hydrolysed poly(ethylene terephthalate) (PET) fabrics and films and bis(benzoyloxyethyl) terephthalate (3PET) endo-wise as shown by MALDI-Tof-MS, LC–UVD/MS, cationic dyeing and XPS analysis. Due to interfacial activation of the lipase in the presence of Triton X-100, a seven-fold increase of hydrolysis products released from 3PET was measured. In the presence of the plasticizer N,N-diethyl-2-phenylacetamide (DEPA), increased hydrolysis rates of semi-crystalline PET films and fabrics were measured both for lipase and cutinase. The formation of novel polar groups resulted in enhanced dye ability with additional increase in colour depth by 130% and 300% for cutinase and lipase, respectively, in the presence of plasticizer.